Chromium Picolinate Modulates Serotonergic Properties and Carbohydrate Metabolism in a Rat Model of Diabetes - Komorowski, James R.; Tuzcu, Mehmet; Şahin, Nurhan; Juturu, Vijaya; Orhan, Cemal; Ulas, Mustafa; Şahin, Kazım (Humana Press Inc, 2012)
Chromium picolinate (CrPic) has shown both antidepressant and antidiabetic properties. In this study, the effects of CrPic on serotonergic properties and carbohydrate metabolism in diabetic rats were evaluated. Sixty male Sprague-Dawley rats were divided into four groups. (1) The control group received only standard diet (8 % fat). (2) The CrPic group was fed standard diet and CrPic (80 mu g CrPic per kilogram body mass (b.m.)/day), for 10 weeks (microgram/kilogram b.m./day). (3) The HFD/STZ group fed a high-fat diet (HFD, 40 % fat) for 2 weeks and then received streptozotocin (STZ, 40 mg/kg, i.p.) (i.v.) HFD-STZ-CrPic group treated as the previous group and then were administered CrPic. CrPic administration to HFD/STZ-treated rats increased brain chromium levels and improved all measurements of carbohydrate metabolism and serotonergic properties (P < 0.001). CrPic also significantly increased levels of insulin, tryptophan, and serotonin (P < 0.001) in the serum and brain, and decreased cortisol levels in the serum (P < 0.01). Except chromium levels, no significant effect of CrPic supplementation was detected on the overall measured parameters in the control group. CrPic administration was well tolerated without any adverse events. The results support the use of CrPic supplementation which improves serotonergic properties of brain in diabetes.
Keywords: Chromium; Glucose; Insulin; Cortisol; Serotonin; Tryptophan